Determination of training needs for water users associations in Gezira Scheme, Sudan - H. E, Musa; A. M. Khalid, Abdel Gader (Gezira Journal of Agricultural Science, 2013)
124 The main objective of the study was to determine the training needs for Water Users Associations (WUAs) in order to suggest appropriate training programs. Seven irrigation divisions were selected randomly from 21 irrigation divisions (Wad Elnaw,Wad Elbur, Tabat, Kab Elgidad,  Shalaie, Wad Elmansi and Gaboja).  A questionnaire was designed to collect the required data by using random sample technique from 395 farmers. The information was collected during the period from April to July 2010.The data were statistically analyzed using the statistical package for social science (SPSS) to calculate frequency, percentages, mean and standard deviation. A Likert scale was used to determine the needed level of training. The study revealed that the previous training courses, training content and duration were neither suitable nor sufficient, because the training courses were concise, short and irrelevant to farmers training needs. In addition, the study revealed that the vast majority of Gezira Scheme farmers preferred practical oriented methods (field demonstrations and field days) to encourage the WUAs to adopt new technology in the irrigation of fields to develop skills, upgrade knowledge and bring positive change among farmers. The study showed that most of farmers were not convinced with the WUAs performance, and that there is a strong need for regular and intensive training programs to raise WUAs capacity regarding management and proper use of irrigation water; rules and regulations; operation and maintenance of irrigation canals; water request and crops water requirement; and water management and water supply contract. All farmers need active participation in water charge, cost recovery and participation in crop choice. This participation must be based on planning of appropriate training programs that consider farmers training needs and                                            .